Dominant Role of Temperature in Drying Kinetics of Magnetite Pellet: Experimental and Modeling Study - Xunrui Liu; Manman Lu; Hanquan Zhang (Metals)
Natural magnetite ore is commonly used to produce oxidized pellets as the raw material for blast furnace ironmaking. The drying of green pellets significantly affects the quality of oxidized pellets. However, the drying process in the traveling grate cannot be directly analyzed. To address this issue, in this study the influences of the drying medium temperature, medium velocity, and pellet diameter on the moisture removal, as well as the drying kinetics of the natural magnetite oxidized pellets were investigated. Orthogonal experimental results indicated that the drying medium temperature had the most significant effect on the drying rate, followed by the medium velocity, while the interaction between the pellet diameter and temperature had a minor influence. Drying kinetic model fitting revealed that the drying process followed a modified Page model (III). Model validation demonstrated that the experimental measurements closely aligned with the theoretical predictions, confirming that the Page model (III) accurately predicted the effects of the drying temperature and medium velocity on the pellet moisture content. Higher drying temperatures further improved the prediction accuracy. The findings provide valuable insights for analyzing and optimizing the drying process of the natural magnetite oxidized pellets in the industrial traveling grate systems.